Pengembangan Alat Evaluasi Berbasis Guided Discovery Learning untuk Mengukur Kemampuan Berpikir Kritis Siswa SMA Kelas X: Development of Evaluation Tools Based on Guided Discovery Learning to Measure the Critical Thinking Skill of High School Students in Class X - Ari Frianto; Risnita Risnita; Maison Maison (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2019)
Students' critical thinking skills can be formed through guidance in the learning process. For this reason, teachers should be aware of the development of their students' critical thinking skills. This study aims to develop a valid, effective and practical evaluation instrument on work and energy subject. The research used a 4-D model which includes the stages of defining, designing, developing and defining. The results are in the form of an essay test instrument with a subject validation value of 42 (very good/valid) and design validation obtained a value of 57 (very good/valid). Limited trials achieved a score of 54 (very practical). Field trials on 29 students recorded 15 students in the category of having good and very good critical thinking skills and 14 students having less critical thinking skills. The trial results show an increase in students' critical thinking skills using guided discovery learning models. The resulted evaluation instrument is categorized as valid, effective, and practical to be used to measure students' critical thinking skills.